2021
DOI: 10.3390/molecules26134068
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Nature of Chemical Bonds by Atomic Force Microscopy

Abstract: The nature of the chemical bond is important in all natural sciences, ranging from biology to chemistry, physics and materials science. The atomic force microscope (AFM) allows to put a single chemical bond on the test bench, probing its strength and angular dependence. We review experimental AFM data, covering precise studies of van-der-Waals-, covalent-, ionic-, metallic- and hydrogen bonds as well as bonds between artificial and natural atoms. Further, we discuss some of the density functional theory calcul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 95 publications
0
8
0
Order By: Relevance
“…For the DFT-simulated, intact molecule, the charge accumulation between the molecule and surface is much less pronounced, whereby the intramolecular contrast of the molecular structure is more distinct, as known for physisorbed molecules (Figure S3). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the DFT-simulated, intact molecule, the charge accumulation between the molecule and surface is much less pronounced, whereby the intramolecular contrast of the molecular structure is more distinct, as known for physisorbed molecules (Figure S3). …”
Section: Resultsmentioning
confidence: 99%
“…In the present study, we investigate the adsorption and heat-induced dehydrogenation reactions of melamine and melem molecules on a Cu(111) surface (Figure a–c). For the structural characterization, we performed ultrahigh-resolution nc-AFM experiments using an O-terminated copper tip (CuOx-tip). , Such an atomically defined functionalized probe tip effectively passivates the tip apex, which allows imaging in the repulsive force regime where a drastically increased resolution can be obtained. The application of this powerful technique to functional organic layers relevant in heterogeneous catalysis could help to identify local reactive sites. These experiments are complemented by STM imaging, XPS analyses and density functional theory (DFT)-based simulations.…”
Section: Introductionmentioning
confidence: 99%
“…To test a single chemical bond, AFM is operated in the condition of an ultrahigh vacuum with a low temperature which is commonly at a liquid helium temperature of 4 K [14]. In the experiment, frequency modulation (FM-) AFM whose cantilever oscillates at frequency f with a fixed amplitude A is chosen.…”
Section: Methods Of Experiments and Results About Covalent Bondsmentioning
confidence: 99%
“…A series of calculations and the experimental demonstrated that highly stiff cantilevers and amplitudes help to stabilize oscillations and maximize the short-range force contribution respectively to optimize the signal-to-noise ratio [14].…”
Section: Methods Of Experiments and Results About Covalent Bondsmentioning
confidence: 99%
See 1 more Smart Citation